Multi-channel experimental and theoretical approach to study the 12C(18O, 18F)12B single charge exchange reaction. (1st March 2023) - Spatafora, A; Carbone, D; Cappuzzello, F; Cavallaro, M; Acosta, L; Agodi, C; Amador-Valenzuela, P; Borello-Lewin, T; Brischetto, G A; Calabrese, S; Calvo, D; Capirossi, V; et al.
Abstract: The broad network of nuclear reactions populated in the 18 O + 12 C collision was studied to test the capability of state-of-art nuclear structure and reaction theories to describe both the direct and sequential components of the ( 18 O, 18 F) single charge exchange nuclear reaction. The experiment was performed using the 18 O beam at 275 MeV incident energy produced by the K800 superconducting cyclotron and the MAGNEX magnetic spectrometer at the Laboratori Nazionali del Sud of the Istituto Nazionale di Fisica Nucleare. A unique comprehensive and coherent theoretical calculation, able to describe the whole network of direct reactions, is the approach proposed for the first time to analyse this large set of experimental data. This holistic approach, applied both to the experimental and theoretical analysis, is the main feature and novelty of the work here presented.